Development of innovative environmental applications of attapulgite clay - Zotiadis, V.; Argyraki, A. (Bulletin of the Geological Society of Greece, 2013)
In this paper we present a series of laboratory and field, pilot- scale applications of attapulgite clay as an amendment for the stabilization of metals in contaminated soil and sewage sludge. Attapulgite’s structure together with its fine particle size and fibrous habit are responsible for its high specific surface area and sorption properties. A pilot scale application of attapulgite clay as a binder for in situ stabilization of toxic metals in contaminated land showed significant reduction in the water leachable metal fraction (Cu: 17%, Pb: 50%, Zn: 45%, Cd: 41%, Ag: 46%, As: 18%, Mn: 47%, Ba: 45%, Sb: 29%). In a second pilot scale environmental application, an innovative attapulgite “Geosynthetic Reactive Clay - GRC” was designed and developed for “capping” and “stabilization”of toxic metals in contaminated soil. Also, laboratory scale experiments with fresh sewage sludge from a municipal water treatment plant showed that addition of attapulgite clay in sludge, significantly reduced the leachable concentrations of phenol, DOC, Hg, Cu, Mo, Pb, Se, As, Zn and pathogen population over a 4 weeks observation period. The developed soil remediation techniques are promising and cost-effective under present market conditions. Concerning treatment of sewage sludge, attapulgite clay is an effective additive that could enhance the composting procedure creating an environmental added value, final compost product.